Profile of Fruit Consumption and Utilization of Jamu by Housewives in Cicanir and Jatipamor Villages in the Era of Germas and Fit with Jamu - Djunaedi, Diah Dhianawaty; Heryaman, Henhen -; Syamsunarno, Mas Rizky Anggun Adipurna; Dahlan, Anisah - (Pharmauho: Jurnal Farmasi, Sains, dan Kesehatan, 2020)
Healthy Lifestyle (Germas) and Fit with Jamu action (Bude Jamu) are the programs to improve health, which promote physical activities, consumption of fruits and vegetables, and the utilization of jamu. The figure of the mother in the family comes in the role of regulating a good diet for the family. In connection with these two programs, study was conducted to determine the profile of fruits consumption and utilization of jamu among housewives in Cicanir and Jatipamor villages, using the cross-sectional design with the number of respondents based on the number of minimum requirements in its activities. 150 Housewives were involved and given questions about the frequency of buying fruit, the favorite fruit, the habit of drinking jamu. The results were that most respondents bought fruit twice a week, their favorite fruits included orange, banana. People who drank jamu in Cicanir and Jatipamor were 40.79% and 25.86%, with the aim of disease prevention was 96.77% and treatment disease was 46.66%. Jamu gendong was the main source of jamu that was utilized, besides that the expertise in making jamu was still practiced and maintained by some respondents. In conclusions, fruit consumption in Cicanir and Jatipamor was quite good. Housewives in Cicanir and Jatipamor used jamu for the purpose of preventing and treating diseases. Jamu gendong was the most widely used source of jamu and the expertise in making jamu is still maintained. These all showed that the culture of Germas and Bude jamu have been applied in the lives of respondents.